2010
DOI: 10.1002/anie.200907108
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Azaspirocycles and their Evaluation in Drug Discovery

Abstract: In modern drug discovery, high-throughput screening may generate promising lead compounds that are less than ideal with respect to important parameters such as absorption, distribution, metabolism, and excretion (ADME). In the process of lead optimization, various structural features are fine-tuned and physicochemical properties such as the basicity (pK a [1] ), lipophilicity (logD), solubility (Sol int ), and clearance rates (CL int ) are improved.[2] Herein, we introduce heteroatom-substituted spiro [3.3]hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(125 citation statements)
references
References 22 publications
0
121
0
1
Order By: Relevance
“…[1][2][3][4] In particular, azetidines, oxetanes and cyclobutanes have attracted much attention in drug discovery and have been introduced to modify the biological profile or the pharmacokinetic properties of new drugs. [5][6][7][8][9][10][11][12][13][14] These cycles can be found in antibacterial agents, protein kinase inhibitors, and in radiotracer ligands ( Figure 1). [8,11,12] The synthesis of such strained cycles has been well documented, [1][2][3][4] and the main direct routes are based on cyclization or cycloaddition reactions of functionalized substrates and functionalization of four-membered cyclic ketones.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In particular, azetidines, oxetanes and cyclobutanes have attracted much attention in drug discovery and have been introduced to modify the biological profile or the pharmacokinetic properties of new drugs. [5][6][7][8][9][10][11][12][13][14] These cycles can be found in antibacterial agents, protein kinase inhibitors, and in radiotracer ligands ( Figure 1). [8,11,12] The synthesis of such strained cycles has been well documented, [1][2][3][4] and the main direct routes are based on cyclization or cycloaddition reactions of functionalized substrates and functionalization of four-membered cyclic ketones.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with imatinib, the 4-methylpiperazin-1-yl of Thiotanib has been changed to 2-thia-6-azaspiro [3.3] heptan-6-yl. Previous studies indicated that the important pharmacokinetic properties of heteroatomsubstituted spiro [3.3] heptanes such as lipophilicity and metabolic stability may be advantageously altered when compared with their traditional piperidine, piperazine, or thiomorpholine counterparts (Burkhard et al 2010). Interestingly, this modulating did not affect the bio-effects of Thiotanib.…”
Section: Discussionmentioning
confidence: 93%
“…The preparation of diazaspiro [3.3] heptane 5 [16] by intramolecular alkylation triggered with tBuOK in THF, evidences that four-membered heterocyclization is also possible with tert-butanesulfinamide nucleophiles, but such reactions are not common. By contrast, five-membered ring formation by displacement of a halide leaving group is far more usual and has been implemented in several ways (Scheme 2).…”
Section: Reactions Involving Metallated N-tert-butanesulfinamides As mentioning
confidence: 99%